Development of a prognostic model to identify the metastatic nasopharyngeal carcinoma patients who may benefit from chemotherapy combination PD-1 inhibitor - Liu, Guo-Ying; Lu, Nian; Bei, Wei-Xin; Li, Wang-Zhong; Liang, Hu; Xia, Wei-Xiong; Xiang, Yan-Qun; Yao, He-Rui (Frontiers in Immunology, 2023)
Background We aimed to establish a prognostic model to identify suitable candidates for chemotherapy combination PD-1 inhibitor in metastatic nasopharyngeal carcinoma (NPC) patients. Patients and methods In this retrospective study, we included 524 patients (192 patients treated with chemotherapy combination PD-1 inhibitor and 332 received chemotherapy alone as first-line regimen) with metastatic NPC between January 2015 and March 2021. We developed a prognostic model to predict progression-free survival (PFS). A model-based trees approach was applied to estimate stratified treatment effects using prognostic scores and two well-matched risk groups (low-risk and high-risk) were created using propensity score matching. Results A prognostic nomogram was established with good accuracy for predicting PFS (c-index values of 0.71; 95% confidence interval, 0.66-0.73). The survival curves were significantly different between low-risk and high-risk groups (median PFS: 9.8 vs. 22.8 months, P < 0.001, respectively). After propensity matching analysis, chemotherapy combination PD-1 inhibitor was significantly associated with superior PFS as compared with chemotherapy alone (median PFS, 10.6 versus 9.3 months, P = 0.016) in the high-risk group. However, no significant difference between chemotherapy combination PD-1 inhibitor and chemotherapy was observed (P = 0.840) in the low-risk groups. Conclusions Our novel prognostic model was able to stratify patients with metastatic NPC into low-risk or high-risk groups and identify candidates for PD-1 inhibitor therapy. These results are expected to be confirmed by a prospective clinical trial.